Meningkatkan Keterampilan Menulis Ringkasan Isi Buku Melalui Model Cooperative Script Dengan Media Gambar Seri - Tamba Siagian (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This type of research is classroom action research. The research was carried out in three cycles with each cycle being carried out in one meeting. The research subjects were fifth grade students and fifth grade teachers at SDN 010082 Pondok Bungur. The results showed that: (1) teacher skills in cycle I got a score of 23 in the good category, cycle II got a score of 28 in the very good category, and cycle III got a score of 30 in the very good category; (2) student activities in the first cycle obtained an average score of 20.3 in the sufficient category, the second cycle obtained a score of 24 in the good category, and the third cycle obtained a score of 29.1 in the very good category; (3) the percentage of classical completeness of writing summaries of book content in the first cycle is 44.4%, the second cycle is 61.1%, and the third cycle is 83.3%. Keywords: cooperative script, series picture  Abstrak: Jenis penelitian ini adalah penelitian tindakan kelas. Penelitian dilaksanakan dalam tiga siklus dengan setiap siklus dilaksanakan dalam satu kali pertemuan. Subjek penelitian adalah siswa kelas V dan guru kelas V di SDN 010082 Pondok Bungur. Hasil penelitian menunjukkan bahwa: (1) keterampilan guru siklus I men-dapat skor 23dengan kategori baik, siklus II mendapat skor 28 dengan kategori sangat baik, dan siklus III mendapat skor 30 dengan kategori sangat baik; (2) aktivitas siswa pada siklus I memperoleh skor rata-rata 20,3 dengan ketegori cukup, siklus II memperoleh skor 24 dengan kategori baik, dan siklus III memperoleh skor 29,1 dengan kategori sangat baik; (3) persentase ketuntasan klasikal keterampilan menulis ringkasan isi buku pada siklus I sebesar 44,4%, siklus II sebesar 61,1%, dan siklus III sebesar 83,3%. Kata Kunci: cooperative script, gambar seri